PBL case writing by students based on early years clinical attachments: a focus group evaluation of a novel approach - Idowu,Y; Muir,E; Easton,G (JRSM Open, 2016)
ObjectivesTo evaluate the perception of medical students of the new approach to problem-based learning which involves students writing their own problem-based learning cases based on their recent clinical attachment, and team assessment.DesignFocus group interviews with students using purposive sampling. Transcripts of the audio recordings were analysed using thematic analysis.SettingImperial College School of Medicine, London.ParticipantsMedical students in the second year of the MBBS course, who attended the problem-based learning case writing session.Main outcome measuresTo elicit the students’ views about problem-based learning case writing and team assessment.ResultsThe following broad themes emerged: effect of group dynamics on the process; importance of defining the tutor’s role; role of summative assessment; feedback as a learning tool and the skills developed during the process.ConclusionsOverall the students found the new approach, writing problem-based learning cases based on patients seen during their clinical attachments, useful in helping them to gain a better understanding about the problem-based learning process, promoting creativity and reinforcing the importance of team work and peer assessment which are vital professional skills. Further tutor development and guidance for students about the new approach was found to be important in ensuring it is a good learning experience. We hope this evaluation will be of use to other institutions considering introducing students’ case writing to problem-based learning.